A Testis-Derived Hydrogel as an Efficient Feeder-Free Culture Platform to Promote Mouse Spermatogonial Stem Cell Proliferation and Differentiation - Yang, Yan; Lin, Qilian; Zhou, Chengxing; Li, Quan; Li, Ziyi; Cao, Zhen; Liang, Jinlian; Li, Hanhao; Mei, Jiaxin; Zhang, Qihao; Xiang, Qi; Xue, Wei; et al. (Frontiers in Cell and Developmental Biology, 2020)
Fertility preservation and assisted reproductive medicine require effective culture systems for the successful proliferation and differentiation of spermatogonial stem cells (SSCs). Many SSC culture systems require the addition of feeder cells at each subculture, which is tedious and inefficient. Here, we prepared decellularized testicular matrix (DTM) from testicular tissue, which preserved essential structural proteins of testis. The DTM was then solubilized and induced to form a porous hydrogel scaffold with randomly oriented fibrillar structures that exhibited good cytocompatibility. The viability of SSCs inoculated onto DTM hydrogel scaffolds was significantly higher than those inoculated on Matrigel or laminin; and intracellular gene expression and DNA imprinting patterns were similar to that of native SSCs. Additionally, DTM promoted SSCs differentiation into round spermatids. More importantly, the DTM hydrogel supported SSCs proliferation and differentiation without requiring additional somatic cells. The DTM hydrogel scaffold culture system provided an alternative and simple method for culturing SSCs that eliminates potential variability and contamination caused by feeder cells. It might be a valuable tool for reproductive medicine.This is a provisional file, not the final typeset article